2015
DOI: 10.1055/s-0035-1558841
|View full text |Cite
|
Sign up to set email alerts
|

Primary Wrist Hemiarthroplasty for Irreparable Distal Radius Fracture in the Independent Elderly

Abstract: Background?Volar plating for acute distal radius fractures (DRF) in the elderly has been recommended. Some studies have suggested that open reduction with internal fixation (ORIF) in this situation results in frequent complications. Our purposes were to provide a definition of irreparable DRF in independent elderly patients and to review the results of a preliminary retrospective series of wrist hemiarthroplasty (WHA) in this patient population. Materials?Between 2011 and 2014, 11 consecutive independent elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Recent studies showed moderate results for wrist hemiarthroplasty in elderly patients following complex DRF [11][12][13][14][15][16][17][18][19][20]. The idea of hemiarthroplasty for this indication was first implemented by Roux in 2005 [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies showed moderate results for wrist hemiarthroplasty in elderly patients following complex DRF [11][12][13][14][15][16][17][18][19][20]. The idea of hemiarthroplasty for this indication was first implemented by Roux in 2005 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the patients had to be aged 65 years or older and living at home performing activities of daily living independently. Surgical treatment was based on the technique described by Herzberg et al [12,21]. A longitudinal incision was made dorsally in line with the third metacarpal bone (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is comparable to complex wrist joint fractures; autonomous elderly patients with AO type “C 2/3” are good candidates to primary prosthetic surgery. The radial resurfing hemiarthroplasty with or without replacement of distal radius metaphysis using the Sophia (Biotech, Paris, Frankreich) implant [ 8 , 9 ], the radial component of RE-MOTION (Small Bone Innovations, Morrisville, Pennsylvania, USA) total wrist [ 10 ], the “Cobra” (Groupe Lépine, Lyon, France) implant [ 10 ], and the “Prosthelast” (Argomedical, Cham, Switzerland) implant [ 11 ] offers a useful alternative to other procedures and may help avoid secondary procedures related to posttraumatic wrist joint and DRUJ OA. Radial hemiwrist implants may also help avoid the main problem of carpal component failure in TWA.…”
Section: Discussionmentioning
confidence: 99%